(untitled) (Bangladesh Journal of Plant Taxonomy, 2007)
Not available. Key words: Pleurocarpous mosses, Hypnobryales, Plagiotheciaceae, Bangladesh DOI: 10.3329/bjpt.v14i1.527 Bangladesh J. Plant Taxon. 14(1): 79-82, 2007 (June)